Summary of Existing Models of the Ni‐P Coating Electroless Deposition Process. Issue 11 (28th August 2013) - Stankiewicz, A.; Szczygieł, I.; Szczygieł, B.
ABSTRACT Electroless nickel‐phosphorous plating is a technique often employed in preparation of protective, decorative, and functional coatings. Several feasible mechanisms are discussed in the literature. The influence of process parameters on metal coating deposition is analyzed and described. Nevertheless, some basics of the process and the fundamental aspects of plating still not explained. A number of research groups make an effort to provide a description of the process with a physical model. The aim is to design a theoretical model that could be valid under operating conditions on a practical scale. This work gives a short review of the published data on the mechanism and kinetics of the electroless Ni‐P deposition process. The review also touches a novel approach—proposition to analyze data using artificial intelligence tools.